Effect of Swim Up Techniques on Sperm Motility and DNA Integrity Versus Unprepared Semen - AL-Marayaty, Shatha S.; Saeed, Ghassan T.; AL-Ahmed, Hazim I. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: The need for assisted reproduction technologies (ART) for the establishment of pregnancies has steadily increased worldwide. Therefore, it is of vital importance that an efficient sperm preparation technique used for retrieval of high-quality spermatozoa contributes to the creations of high-quality embryos, with high implantation potential.Objective: to study the effect of swim up technique on human sperm motility and DNA integrity.Subject and methods: A prospective study carried on 70 samples of human semen; each sample, divided into 2 parts, one part was prepared by swim-up technique and the other not, and then study sperm motility and DNA integrity in both parts. Sperm DNA integrity was determined using a modified alkaline single cell gel electrophoresis (comet) assay and acridine orange test (AOT), and motility was determined by light microscope.Result(s): the results showed that swim up technique give a significant. increasing in motility percentage and a significant. decreasing in DNA damage (P< 0.05) than unprepared human sperm.Conclusion(s): Swim up technique for sperm preparation is increasing motility and decreasing DNA damage.